Partisipasi Masyarakat Kota Pekanbaru terhadap Peredaran Sediaan Farmasi Tanpa Izin Edar oleh Balai Besar Pengawas Obat dan Makanan dalam Perspektif Undang-Undang Nomor 17 Tahun 2023 Tentang Kesehatan - Sari, Etika; Maya Lestari, Maria; Jaya Kusuma, Zulfikar (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2025)
Circulation of pharmaceutical preparations without a distribution permit is a serious problem that has attracted the attention of the Food and Drug Administration (BBPOM) in Indonesia. Unregistered pharmaceutical preparations can endanger public health because their safety, efficacy and quality are not guaranteed. Referring to Article 138 of Law no. 17 of 2023 concerning Health, BBPOM has the responsibility to supervise and ensure that all pharmaceutical preparations meet the specified standards. However, the effectiveness of such supervision is highly dependent on community participation, which is regulated in Article 417 paragraph (1) of the same law.This type of research is empirical legal research, namely research with field data as the main data source. The research location is in Pekanbaru City, the researcher chose this research location because there are still many pharmaceutical preparations in circulation without distribution permits which are distributed to the people of Pekanbaru City. In this research, the population used as the Pekanbaru community in the circulation of pharmaceutical preparations is 411,100 people. So the number of samples used was 300 people. Factors that influence public participation include the level of knowledge regarding pharmaceutical preparations, awareness of the risks of drugs without distribution permits, as well as access to information and trust in government institutions. Additionally, socio- economic factors such as price and accessibility of healthcare services also play an important role. Health education curricula that lack emphasis on the safety of pharmaceutical preparations, along with the role of mass media in shaping public perceptions, contribute to this problem.